Penafsiran Surat Al-Falaq [113]: 3-4 : Menurut Abd. Ar-Rauf As-Singkili, Hamka dan M. Quraish Shihab: Telaah Atas Epistemologi dan Genealogi - Wendi Parwanto (Pascasarjana Institut Ilmu Al Quran (IIQ) Jakarta, 2018)
Many assumptions say that differences in generation, educational background, socio-cultural background and so on will have an effect on the mindset of an interpreter. To prove the validity of these assumptions, this study proposed to explore the epistemology structure of QS. al-Falaq [113]: 3-4 interpretation in Tarjuman al-Mustafid by Abd. as-Singkili, Tafsir Al- Azhar by HAMKA and Tafsir Al-Misbah by M. Quraish Shihab. The results of this study are any differences in the epistemological structure of interpretation between the three interpreters in interpreting Qs. al-Falaq [113]: 3-4, for example in terms of sources, As-Singkili uses hadith and ra'yu, HAMKA uses munasabah, hadith, ulama opinions and ra'yu. , while M Qurasih Shihab uses lexical-linguistic analysis, munasabah, hadith, ulama opinion and ra'yu.